THE PROFILE OF JUNIOR HIGH SCHOOL STUDENTS’ CONCEPTUAL UNDERSTANDING OF MOTION AND FORCE - Enik Nirina (Jurnal Pembelajaran Sains, 2023)
This research analyzed the percentage of junior high school students' conceptual understanding of the topics of motion and force. The study employed a quantitative method with a sequential explanatory design and was conducted at SMP Negeri 1 Kamal. The population consisted of all grade VII students during the 2023/2024 academic year. The sampling technique used was purposive sampling, resulting in a sample of 28 students. Data collection methods included tests, non-test instruments, observations, and documentation. The indicators of conceptual understanding in this study included interpreting, exemplifying, classifying, inferring, and explaining. Based on the results, it was concluded that: (1) The percentage of students' conceptual understanding is generally low, averaging only 25%; (2) The highest percentage was observed in the interpreting indicator at 52%, while the lowest was in the exemplifying indicator at 4%.